2004
DOI: 10.1542/peds.113.5.1279
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyponatremia Related to Intravenous Fluid Administration in Hospitalized Children: An Observational Study

Abstract: The most important factor for hospital-acquired hyponatremia is the administration of hypotonic fluid. We suggest that hypotonic fluid not be given to children when they have a P(Na) <138 mmol/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
176
3
18

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(207 citation statements)
references
References 47 publications
8
176
3
18
Order By: Relevance
“…The incidence of hyponatremia with the use of hypotonic intravenous fluids has ranged from 7.6% to 57% [9][10][11][12][13]. We observed unusually high incidence of 70% hyponatremia with the use of hypotonic 'standard volume' maintenance fluid in a selected group of nonsurgical pediatric patients.…”
Section: Discussionmentioning
confidence: 73%
“…The incidence of hyponatremia with the use of hypotonic intravenous fluids has ranged from 7.6% to 57% [9][10][11][12][13]. We observed unusually high incidence of 70% hyponatremia with the use of hypotonic 'standard volume' maintenance fluid in a selected group of nonsurgical pediatric patients.…”
Section: Discussionmentioning
confidence: 73%
“…The investigators observed more dehydration in the group receiving half maintenance than in that receiving full maintenance. In a retrospective case-control study, higher IV fluid rate and amount were associated with hyponatremia (Na <136 mmol/L); patients with hyponatremia received a higher rate of electrolyte-free fluid (2±2 mL/kg/h vs. 1±1 mL/kg/h; P<0.001) and more commonly received greater than the recommended maintenance rate (73 vs. 23 %; P<0.001) [38]. As mentioned previously, Saba et al reported that when maintenance fluids were delivered at the appropriate rate and pre-existing volume deficits were corrected, hypotonic fluids were not associated with an increased risk for hyponatremia [31].…”
Section: Bmaintenance^fluid Rate and Hyponatremiamentioning
confidence: 99%
“…1 The rate of fall of the plasma sodium appears to be as important a factor as the magnitude of the reduction and plasma sodium is frequently normal at baseline. 4 It is recognized that children may be susceptible to developing the problems associated with hyponatraemia at higher concentrations of sodium than adults. 1 Fatal cerebral oedema was associated with a fall in sodium of as little as 6 mmol/L over 9 h (137--131mmol/L) in an 8-week-old infant, 5 and a fall of 17 mmol/L (137--120 mmol/L) over 12 h in a child aged 13 months.…”
Section: Introductionmentioning
confidence: 99%